The Portuguese economic crisis is associated with socioeconomic and sex disparities on children's health‐related behaviors and obesity: A cross‐sectional study. Issue 12 (7th September 2022) - Rodrigues, Daniela; Machado‐Rodrigues, Aristides; Gama, Augusta; Nogueira, Helena; Silva, Maria‐Raquel G.; Padez, Cristina
Abstract: Objectives: Our objective was to examine the relationship between the 2008 and 2015 economic crisis and children's physical activity (PA) outcomes, eating behaviors and obesity prevalence, while considering sex inequalities and familial socioeconomic status. Method: This is a cross‐sectional study, including data collected in 2016/2017 among 5134 children aged 6–11 years (mean age: 8.11 ± 1.24; 50.0% boys). Children's height, weight, and waist circumference were objectively measured. Children's sleep‐ and screen‐time, participation in organized sports, and specific dietary habits were reported parental‐reported using a standardized questionnaire. An economic crisis impact score, with data from 10 indicators of economic needs in the family, was used to characterize the crisis' impact. Results: First, the prevalence of overweight and obesity was higher in children whose families had a higher impact of the crisis. Second, children's intake of fruit and high‐fat food, screen‐time, sleep‐time, and participation in organized sports differed according to the level of impact of the economic crisis. Third, the association between health‐related behaviors and the impact of the economic crisis was stronger for girls compared to boys. Conclusion: Our findings give us an indication of how economic crises may drive changes in health outcomes.